Surface modulation of silicon nitride ceramics for orthopaedic applications. (15th October 2015) - Bock, Ryan M.; McEntire, Bryan J.; Bal, B. Sonny; Rahaman, Mohamed N.; Boffelli, Marco; Pezzotti, Giuseppe
Graphical abstract: Abstract: Silicon nitride (Si3 N4 ) has a distinctive combination of material properties such as high strength and fracture toughness, inherent phase stability, scratch resistance, low wear, biocompatibility, hydrophilic behavior, excellent radiographic imaging and resistance to bacterial adhesion, all of which make it an attractive choice for orthopaedic implants. Unlike oxide ceramics, the surface chemistry and topography of Si3 N4 can be engineered to address potential in vivo needs. Morphologically, it can be manufactured to have an ultra-smooth or highly fibrous surface structure. Its chemistry can be varied from that of a silica-like surface to one which is predominately comprised of silicon-amines. In the present study, a Si3 N4 bioceramic was subjected to thermal, chemical, and mechanical treatments in order to induce changes in surface composition and features. The treatments included grinding and polishing, etching in aqueous hydrofluoric acid, and heating in nitrogen or air. The treated surfaces were characterized using a variety of microscopy techniques to assess morphology. Surface chemistry and phase composition were determined using X-ray photoelectron and Raman spectroscopy, respectively. Streaming potential measurements evaluated surface charging, and sessile water drop techniques assessed wetting behavior. These treatments yielded significant differences in surface properties with isoelectric points ranging from 2 to 5.6, and moderate to extremely hydrophilic water contact angles from ∼65° to ∼8°. This work provides a basis for future in vitro and in vivo studies which will examine the effects of these treatments on important orthopaedic properties such as friction, wear, protein adsorption, bacteriostasis and osseointegration. Statement of Significance: Silicon nitride (Si3 N4 ) exhibits a unique combination of bulk mechanical and surface chemical properties that make it an ideal biomaterial for orthopaedic implants. It is already being used for interbody spinal fusion cages and is being developed for total joint arthroplasty. Its surface texture and chemistry are both highly tunable, yielding physicochemical combinations that may lead to enhanced osseointegration and bacterial resistance without compromising bulk mechanical properties. This study demonstrates the ease with which significant changes to Si3 N4 's surface phase composition, charging, and wetting behavior can be induced, and represents an initial step towards a mechanistic understanding of the interaction between implant surfaces and the biologic environment.